Hospitalist perspectives on barriers to recommend and potential benefit of the COVID-19 vaccine. Issue 4 (8th August 2021) - Dugani, Sagar B.; Geyer, Holly L.; Maniaci, Michael J.; Fischer, Karen M.; Croghan, Ivana T.; Coons, Trevor J.; Canan, Elizabeth L.; Burton, M. Caroline
ABSTRACT: Background : Hospitalists, comprised of nurse practitioners and physician assistants (collectively, advanced practice providers [APPs]) and physicians, have opportunities to counsel patients and reduce SARS-CoV-2 related coronavirus disease 2019 (COVID-19) vaccine hesitancy. However, hospitalist perspectives on the COVID-19 vaccine and potential differences between APPs and physicians are unknown. Understanding hospitalist perspectives could help to address vaccine hesitancy among patients. Methods : We conducted an online survey of hospitalists at Mayo Clinic sites in Arizona, Florida, Minnesota, and Wisconsin from 14 December 2020 through 4 January 2021. We collected demographic information and assessed perspectives on the COVID-19 vaccine and, for comparison, on the influenza vaccine. Descriptive statistics were used to compare responses between APPs and physicians. Results : The overall response rate was 42.7% (n = 128/300) and comprised of 53.9% women (n = 69/128) and 41.4% APPs (n = 53/128). Most hospitalists reported receiving or planning to receive vaccination against COVID-19 (93.7%; n = 119/128) and influenza (97.7%; n = 125/128). Most hospitalists reported they would advise 100% of patients to receive the COVID-19 vaccine (66% for APPs; 74.7% for physicians) and influenza vaccine (83% for APPs; 80% for physicians). Barriers to recommending the COVID-19 vaccine included patient health status and vaccine safety profile. Hospitalists reported that patients and coworkers receiving the COVID-19 vaccine would reduce their anxiety ( 80% of hospitalists), social isolation ( 64% of hospitalists), and improve their emotional support ( 40% of hospitalists). APP and physician responses were similar. The possible reduction in social isolation was associated with higher odds of hospitalists advising all patients to receive the COVID-19 vaccine (adjusted odds ratio 2.95 [95% confidence interval, 1.32–6.59]; P < .008), whereas hospitalist age, gender, and profession showed no association. Conclusion : Most hospitalists would reportedly advise patients to receive the COVID-19 vaccine. Barriers to this recommendation included patient health status and vaccine safety. Hospitalists are an important resource to provide patient education and reduce COVID-19 vaccine hesitancy.